CRITICAL INDUSTRIAL PSYCHOLOGY: WHAT IS IT AND WHERE IS IT? - Islam, Gazi; Zyphur, Michael J (PINS-Psychology in Society, 2025)
In this paper, we apply major trends in critical and post-structuralist theories to the theory and practice of Industrial-Organizational Psychology. We begin with an examination of relevant strands of social theory, moving from a discussion of Weberian institutionalism to the “discursive turn” in Habermas, and finally to a critique of organizational communication in Foucault’s post-structuralist writings. We then apply these general theoretic approaches to the current state of the art in Industrial Organizational Psychology, attempting to show how, despite the lack of integration of these theories in the current literature, key ideas may be relevant to the development of theory. Finally, we attempt to sketch some of the main theoretical and applied considerations that a critical approach to industrial-organizational psychology would take into account.